2012
DOI: 10.1159/000338378
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Obstructive Pulmonary Disease with Cognitive Decline in Very Elderly Men

Abstract: Aim: To determine the change in cognitive function in very elderly men with chronic obstructive pulmonary disease (COPD) over a 3-year period relative to age- and education-matched controls. Methods: In this hospital-based, prospective case-control study, we evaluated a consecutive series of 110 very elderly men with COPD and 110 control subjects who were hospitalized between January and December 2007. All the subjects performed cognitive tests at baseline and underwent annual evaluations (for 3 years), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
(46 reference statements)
1
10
0
2
Order By: Relevance
“…In a small study of young volunteers, acute intermittent hypoxemia was related to decreases in working memory . Individuals with COPD, who have low levels of oxygen saturation, have been shown to have greater cognitive decline than those without COPD, and resting hypoxemia was a strong predictor of incident cognitive impairment in individuals with COPD . The findings of this study, along with results from animal models and COPD studies, suggest that nocturnal hypoxemia is a mechanism for cognitive decline.…”
Section: Discussionsupporting
confidence: 48%
“…In a small study of young volunteers, acute intermittent hypoxemia was related to decreases in working memory . Individuals with COPD, who have low levels of oxygen saturation, have been shown to have greater cognitive decline than those without COPD, and resting hypoxemia was a strong predictor of incident cognitive impairment in individuals with COPD . The findings of this study, along with results from animal models and COPD studies, suggest that nocturnal hypoxemia is a mechanism for cognitive decline.…”
Section: Discussionsupporting
confidence: 48%
“…Chronic obstructive pulmonary disease (COPD) is a chronic lung disease and a major risk factor for cognitive impairment due to chronic hypoxemia. 7,8 It is our opinion that asthma is a chronic lung disorder that may affect cognitive performance, although severity and the duration of illness are important factors to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…As measured by the MMSE, cognitive function significantly declined in people with COPD (mean age of 68 years) over 2 years (Incalzi et al., ). A recent longitudinal study has shown that people with COPD with a mean age ˃80 years had a more rapid rate of cognitive decline over 3 years, based on MMSE scores, word list recall, delayed recall, animal category fluency and symbol digit modalities (Zhou et al., ). Cognitive decline in people with COPD was also reported over 6 years, using a data set from the Health and Retirement Study (Hung, Wisnivesky, Siu, & Ross, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Complementing cross‐sectional studies, a recent longitudinal study has reported that COPD was significantly associated with more rapid cognitive decline over 3 years in patients than in control subjects (Zhou et al., ). Not only does COPD increase the risk of cognitive impairment over time, but individuals who have had COPD more than 5 years had a greater risk of developing cognitive impairment (Rusanen et al., ; Singh et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation